INTEGRASI PENDIDIKAN ANTI NARKOBA DALAM MATA PELAJARAN PPKn DI SMP NEGERI 1 RANTEPAO KABUPATEN TORAJA UTARA - Aco Agus, Andi; Suyitno, Imam; Mesalayuk, Elsa Osing (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
Abstract : This study aims to determine (1) the efforts and strategies of anti-drug education in Civics subjects, (2) supporting factors and inhibiting factors of data through observation, interviews and documentation. The data obtained from the research were collected and processed with qualitative data analysis. The results showed that (1) the efforts and strategies of anti-drug education in Civics subjects are the first to carry out drug counseling in this case the school cooperates with the BNN in conducting counseling on the dangers of drug use. The second is to carry out socialization related to the dangers of drug use carried out by Civics teachers in the learning process and the third is the provision of information or appeals such as posters, paintings related to the dangers of drug use. (2) Supporting factors in anti-drug education are adequate facilities such as a room for drug counseling, a library with a collection of books and materials related to drugs and interactive teaching methods. The inhibiting factors in anti-drug education are the influence of cellphones, unhealthy relationships and limited learning time.